CULTURE SHOCK SISWA BERKEBUTUHAN KHUSUS SELAMA PANDEMI COVID 19 DAN UPAYA PENCEGAHANNYA MELALUI KONSELING MULTIKULTURAL [CULTURE SHOCK STUDENTS WITH SPECIAL NEEDS DURING THE COVID-19 PANDEMIC AND THE EFFORT TO PREVENT IT THROUGH MULTICULTURAL COUNSELING] - Susana Aditiya Wangsanata; Dwi Vianita Rosari; Sucik Rahayu (Perkumpulan Ahli Bimbingan Konseling Islam Indonesia, 2021)
The purpose of this study is to describe and find out radically or deeply about the phenomenon of culture shock on students with special needs during the COVID-19 pandemic and its prevention efforts through multicultural counseling. The research used qualitative approach with literature study research design. The results of this study found the answer that culture shock did occur and was experienced by students with special needs during the COVID-19 pandemic. Based on the reality on the ground, students with special needs experience problems in the online learning process. Although there is no scientific data and research, the phenomenon of culture shock has become a common problem caused by the COVID-19 pandemic, including those experienced by students with special needs. Therefore, the phenomenon and problems of culture shock need to get the right treatment by using multicultural counseling. Multicultural counseling with the same model as counseling in general, but paying more attention to the counselee's cultural background, to be able to do counseling well. Thus, there is an appropriate meeting point between the problems experienced and the treatment used, namely the different cultural problems during the COVID-19 pandemic.